2007
DOI: 10.1287/mnsc.1070.0711
|View full text |Cite
|
Sign up to set email alerts
|

Loss Aversion Under Prospect Theory: A Parameter-Free Measurement

Abstract: International audienceA growing body of qualitative evidence shows that loss aversion, a phenomenon formalized in prospect theory, can explain a variety of field and experimental data. Quantifications of loss aversion are, however, hindered by the absence of a general preference-based method to elicit the utility for gains and losses simultaneously. This paper proposes such a method and uses it to measure loss aversion in an experimental study without making any parametric assumptions. Thus, it is the first to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
515
6
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 679 publications
(553 citation statements)
references
References 51 publications
(125 reference statements)
29
515
6
3
Order By: Relevance
“…Our estimates are closer to linearity as compared to the parametric studies of Harrison and Rutström (2009) and Donkers et al (2001), who found (α,β) = (.71, .72) and (.61, .61) respectively, which suggests that their parametric specifications may be inappropriate for separating utility from probability weighting. The estimates confirm diminishing sensitivity, both with respect to losses and to gains (Tversky and Kahneman 1992;Abdellaoui 2000;Abdellaoui et al 2007b), and we cannot reject equal curvature in both domains in favor of the more recent hypothesis of partial reflection (Wakker et al 2007). These results are qualitatively similar to those obtained by Booij and van de Kuilen (2007).…”
Section: Utility Curvaturecontrasting
confidence: 56%
See 3 more Smart Citations
“…Our estimates are closer to linearity as compared to the parametric studies of Harrison and Rutström (2009) and Donkers et al (2001), who found (α,β) = (.71, .72) and (.61, .61) respectively, which suggests that their parametric specifications may be inappropriate for separating utility from probability weighting. The estimates confirm diminishing sensitivity, both with respect to losses and to gains (Tversky and Kahneman 1992;Abdellaoui 2000;Abdellaoui et al 2007b), and we cannot reject equal curvature in both domains in favor of the more recent hypothesis of partial reflection (Wakker et al 2007). These results are qualitatively similar to those obtained by Booij and van de Kuilen (2007).…”
Section: Utility Curvaturecontrasting
confidence: 56%
“…Their properties are described extensively in Abdellaoui et al (2007a). Unfortunately, a commonly accepted definition of loss aversion does not exist in the literature (Abdellaoui et al 2007b). The framework that we employ, used by Tversky and Kahneman (1992), defines loss aversion implicitly as:…”
Section: Parametric Specificationsmentioning
confidence: 99%
See 2 more Smart Citations
“…An empirical study of Guo's model is beyond the aim of the present paper. However, we refer the interested reader to papers that have estimated similar models, finding values of λ either in the range of 1.4-5 (see Table 1 in Abdellaoui et al (2007)) or slightly above 1 Murphy and ten Brincke (2018); Nilsson et al (2011). For a careful and critical review, see, e.g., Harrison and Swarthout (2016).…”
Section: Proportional Insurancementioning
confidence: 99%